Implications of Recent Income Distribution Trends on National Pension Reform Discussions - Heesuk Yun (Korea Development Institute (KDI), 2016)
The maturing of the National Pension scheme has helped improve income distribution recently, but its effect has been limited due to a large coverage gap in the system. Against this backdrop, the focus in pension reform discussions needs to be reset toward enhancing enrollment instead of heightening the replacement ratio. - 172 Growth and distribution in a virtuous cycle after economic development in the 1960s; 173 deteriorating distribution after the early 1990s; and 174 signs of improvement in distribution thanks to redistribution in recent years. - Overall, the poverty rate of respective population groups is declining, and the increase in the senior population is largely to blame for the heightening poverty rate. - The recent reduction in poverty is owing to the maturing of the National Pension. - Public pension benefits 76% of the povertyescaping households in the redistribution process. - The main channel for redistribution through tax expenditures is through public pension payments - The higher public pension's income replacement ratio rise, the more households with no earned income appear. As a result, market income inequality would worsen and redistribution will seemingly function strongly. - Fixation to income replacement ratio in pension reform discussions originated from certain myths: 172 Korea's income replacement ratio is low, and 173 that is mainly responsible for the old-age poverty. - Households with public pension are 44.6% likely to escape poverty through redistribution, but those without show only a 9.8% likelihood. - The presence of a coverage gap in its pension system is the main reason of Korea having difficulty in reinforcing a redistribution function.
Keywords: 330